Glare and cognitive performance in screen work in the presence of sunlight. (April 2016) - Rodriguez, RG; Yamín Garretón, JA; Pattini, AE
Research concerning the effects of glare on distraction is scarce. We designed a 2 × 2 repeated measures experiment ( n  = 32) in order to examine the influence of a large area glare source and glare sensitivity on reported discomfort glare and cognitive performance. Daylight glare probability was the within-subjects variable and glare sensitivity was the between-subjects variable. We found a statistically significant difference in glare sensation votes between scenarios, without statistically significant differences in glare ratings due to glare sensitivity. We found some statistically significant effects on our participants' reaction times. Also, we calculated their effect sizes, which had practical relevance. Our results encourage further research in an issue that has been suggested since the early stages of glare research but has never been systematically and consistently addressed.